Demographic and socioeconomic factors associated with cervical cancer screening among women in Serbia - Djordjevic, Slavica; Boricic, Katarina; Radovanovic, Snezana; Simic Vukomanovic, Ivana; Mihaljevic, Olgica; Jovanovic, Verica (Frontiers in Public Health, 2024)
Objectives: Effective reduction of cervical cancer incidence and mortality requires strategic measures encompassing the implementation of a cost-effective screening technology. Serbia has made significant strides, introducing organized cervical cancer screening in 2012. However, various impediments to screening implementation persist. The aim of the study was to estimate the socioeconomic factors associated with cervical cancer screening among women in Serbia. Method: Data from 2019 National Health Survey of the population of Serbia was used in this study. The study is cross sectional survey on a representative sample of the population of Serbia. Present total number of participants analyzed in survey 6,747. Results: In Serbia, 67.2% of women have done a Pap test at any time during their lives, of which 46.1% of women have undergone cervical cancer screening in the past three years. About a quarter of women have never undergone a Pap test in their life (24.3%). The probability of never having a Pap test have: the youngest age group (15-24 years) is 1.3 times more likely than the oldest age group (OR=1.31), unmarried women 0.3 times more often than married women (OR=0.37), respondents with basic education 0.9 times more often than married women (OR=0.98), the women of lower socioeconomic status 0.5 times more often than respondents of high socioeconomic status (OR=0.56). Conclusions: Enhancement of the ex-isting CCS would be the appropriate public health approach to decrease the incidence and mortality of cervical cancer in the Republic of Serbia.